Merchant steering of consumer payment choice: Evidence from a 2012 diary survey - Oz Shy; Joanna Stavins (Federal Reserve Bank of Boston, 2014)
This paper seeks to discover whether U.S. merchants are using their recently granted freedom to offer price discounts and other incentives to steer customers to pay with methods that are less costly to merchants. Using evidence of merchant steering based on the 2012 Diary of Consumer Payment Choice, we find that only a very small fraction of transactions received a cash or debit card discount, and even fewer were subjected to a credit card surcharge. Transactions at gasoline stations were more likely to receive either cash discounts or credit card surcharges than transactions in other sectors. Larger-value transactions were somewhat more likely to receive a discount, although the effect is small when controlling for merchant sector. There is little evidence that merchants have started taking advantage of their new flexibility to influence consumers' payment choice by either discounting or surcharging based on the payment method.
Keywords: D14; 330; payment choice; merchant steering; cash and debit discount; credit card surcharge